FACTORS AFFECTING THE IMPLEMENTATION OF THE NURSING PROCESS AMONG NURSES AT ENTEBBE REGIONAL REFERRAL HOSPITAL, WAKISO DISTRICT. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Doreen Ninsiima; Bonny Bukenya (Student's Journal of Health Research, 2023)
Background: In Uganda, the implementation of the nursing process among nurses is still a very big challenge, especially in many government hospitals. Failure to use the nursing process has led to a lack of continuity of patient care hence delaying the recovery process and outcomes. The purpose of the study was to determine the factors affecting the implementation of the nursing process among nurses at Entebbe Regional Referral Hospital, Wakiso district. Methodology: The study used a descriptive cross-sectional study design that used quantitative data collection methods. A convenience sampling method was used to select 32 respondents who responded to semi- structured questionnaires. Data was analyzed and presented using Microsoft Excel Programs that presented it in the form of frequency tables, pie charts, and graphs. Results: Nurse-related factors were; 25(78.1%) knew less than three steps involved in the nursing process, 18(56.3%) strongly disagreed that the nursing process should be mandatory and 30(93.7%) did not have enough time to use the nursing process. Institutional factors were; 24(75%) did not have policies regarding the use of the nursing process, 27(84.4%) were never supported during the use of the nursing process and 32(100%) reported the absence of designed forms for the nursing process. Conclusion: Nurse-related factors ranging from lack of awareness of steps involved in the nursing process, time inadequacy, and negative perceptions towards the nursing process negatively affected the implemen- tation of the nursing process. Institutional factors that hindered the implementation of the nursing process were the absence of designed nursing process forms, lack of motivation, and absence of policies. Recommendations: The Ministry of Health should design and supply standard nursing process documentation sheets and Entebbe Regional Referral Hospital should develop policies pertaining implementation of the nursing process, supervision, and motivation of nurses.